The Effectiveness Of Oketani Massage On The Prevention Of Breast Milk Dams In Postpartum Mothers In The Working Area Of Tanjung Leidong Health Center, North Labuhan Batu Regency - Sari, Dewi; Simamora , Lasria (CV. Devitara, 2023)
Data from the Central Bureau of Statistics in 2018, the percentage of infants aged less than 6 months who get exclusive breastfeeding in Indonesia is 44.36%, this is a decrease compared to 2017 which is 55.96%. Likewise, based on provincial data, North Sumatra province amounted to 33.33%, and decreased compared to 2017, which was 49.83% (Central Statistics Agency. 2018). Nationally, the coverage of babies receiving exclusive breastfeeding in 2020 was 66.06%. This figure has exceeded the 2020 strategic plan target of 40%. The purpose of this study was to determine the effectiveness of Oketani massage on the prevention of breast milk dams in postpartum mothers in the working area of Tanjung Leidong Health Center, North Labuhan Batu Regency. This study used a quasi-experimental method with a Posttest only with control group design, where the study was divided into 2 groups, namely the intervention group and the control group. The research will be conducted May – July 2022. The population in the study was Mrs. Nifas on the first day in the Tanjung Leidong health center work area which amounted to 26 people for the April-July 2022 period, where the author divided the sample into two groups, 13 people as an intervention group and 13 people into a control group. The data analysis used is the Paired T-Test Sample Test, which is to determine the difference in treatment in two samples / treatment groups with the condition that the data is normally distributed. At the limit of the meaning of statistical calculations p < α= 0.05. The results of the Paired t-test analysis obtained p-value = 0.021 showed that oketani massage in postpartum mothers was effective in preventing breast milk dams. It is hoped that the results of this study can be used as one of the complementary therapies in the prevention of breast milk dams.